The High-Rise Private Eyes : The Case of the Troublesome Turtle - Rylant, Cynthia; Karas, G. Brian (New York : Greenwillow Books, 2001)
Bunny and Jack, animal detectives, investigate the disappearance of the balloons from the neighborhood toy store.
Keywords: Animals -- Fiction; Balloons -- Fiction; Football -- Fiction; Mystery and detective stories